Characterization of leaf waste based biochar for cost effective hydrogen sulphide removal from biogas. (February 2018) - Sahota, Shivali; Vijay, Virendra Kumar; Subbarao, P.M.V.; Chandra, Ram; Ghosh, Pooja; Shah, Goldy; Kapoor, Rimika; Vijay, Vandit; Koutu, Vaibhav; Thakur, Indu Shekhar
Graphical abstract: Highlights: Leaf waste biochar was used as an adsorbent for H2 S removal from biogas. Biochar was prepared at different temperatures (200, 300 and 400 °C). Biochar prepared at 400 °C showed highest H2 S removal of 84.2%. SEM images indicate presence of micropores responsible for trapping H2 S molecules. XRD analysis proved the conversion of H2 S into S 0 after removal. Abstract: Installation of decentralized units for biogas production along with indigenous upgradation systems can be an effective approach to meet growing energy demands of the rural population. Therefore, readily available leaf waste was used to prepare biochar at different temperatures and employed for H2 S removal from biogas produced via anaerobic digestion plant. It is found that biochar prepared via carbonization of leaf waste at 400 °C effectively removes 84.2% H2 S (from 1254 ppm to 201 ppm) from raw biogas for 25 min in a continuous adsorption tower. Subsequently, leaf waste biochar compositional, textural and morphological properties before and after H2 S adsorption have been analyzed using proximate analysis, CHNS, BET surface area, FTIR, XRD, and SEM-EDX. It is found that BET surface area, pore size, and textural properties of leaf waste biochar plays a crucial role in H2 S removal from the biogas.